2018
DOI: 10.1016/j.amepre.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Human Rights as Political Determinants of Health: A Retrospective Study of North Korean Refugees

Abstract: Introduction: The gravity, scale, and nature of human rights violations are severe in North Korea. Little is known about the mental health consequences of the lifelong exposures to these violations. Methods: In 2014–2015, a retrospective study was conducted among 383 North Korean refugees in South Korea using respondent-driven sampling to access this hidden population. This study collected information on the full range of political and economic rights violations and measured post-traumatic stress disorder, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In September 2014 and January 2015, a Respondent-Driven Sampling (RDS) design was used to contact North Korean adults newly resettling in urban communities in South Korea [17]. These individuals are not easily accessible due to their concerns about collective punishment of their families left behind in North Korea.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In September 2014 and January 2015, a Respondent-Driven Sampling (RDS) design was used to contact North Korean adults newly resettling in urban communities in South Korea [17]. These individuals are not easily accessible due to their concerns about collective punishment of their families left behind in North Korea.…”
Section: Methodsmentioning
confidence: 99%
“…A five year recall period is used in several large-scale population-based household surveys in low and middle income countries [23]. For human rights violations, however, we exceptionally consider 10 years recall time due to the intensity of the potentially traumatic memory [17].…”
Section: Methodsmentioning
confidence: 99%
“…5 Moreover, the severity of anxiety, depression, and PTSD symptoms in North Korean refugees seems to be similar or even higher than those reported in other major humanitarian emergencies, probably associated with systematic violations of basic human rights (i.e., freedom of thoughts and expression, freedom of movement). 8 Another recent epidemiological study presented that North Korean refugees have higher lifetime prevalence of suicidal thoughts and behaviors not only compared to general population, but also other refugee populations. 9 Therefore, the prevalence and severity of psychological problems-mainly depression, anxiety, and PTSD-are substantially high in North Korean refugees, and this needs to be addressed for their rehabilitation and successful resettlement in South Korea.…”
Section: The Effectiveness Of Cognitive Behavioral Therapy On Depressmentioning
confidence: 99%
“…Many studies showed that depression is experienced by a large number of defectors (Cha, et al 2018;Nam, Kim, DeVylder and Song 2016;Jeon et al 2009;Lee, Min and Jeon 2009;Lee et al 2001;Jeon 2000). A few studies went beyond the presence of the symptom of depression and examined its correlates.…”
Section: Mental Health Of Women and Childrenmentioning
confidence: 99%